Learning experience designs (LEDs) in an age of complexity: time to replace the lightbulb?. Issue 6 (2nd November 2018) - Beard, Colin
ABSTRACT: This paper describes reflective practice research of the action taken to address commonplace teaching issues faced in the higher education classroom. Covering a substantial number of years three very different student learning experiences were ultimately created, each requiring the students to interact with self, knowledge, and others in fundamentally different ways. The first learning experience, termed informational learning, focuses on knowledge acquisition, confidence building, social interaction and the development of the student sense of belonging. The second learning experience, termed relational learning, applies spatial and embodied cognition to develop metacognitive skills. The final learning experience, termed transformational learning, emphasises personal transformation brought about by dissonance work at the emotion laden 'edge'. Together the three phases highlight how practitioner Action Research can generate Living Theory through the understanding of the complex, multi-disciplinary ecology of the practice-theory dynamic. The paper challenges simplistic notions of teaching, highlighting how the natural, human, and social sciences all contribute to the holistic understanding of the design of learning experiences. The findings have potential for wider application for module and curricula designs.